The Role of Corporate Social Responsibility (CSR) in Mining Company Disputes Based on Limited Liability Company Law and Mineral and Coal Mining Law - Hutrin Kamil; Moh. Faizur Rohman (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2024)
A company's commitment to act morally, conduct business legally, and improve the lives of local communities and society at large is known as corporate social responsibility (CSR). In the mining industry itself, the implementation of CSR is an interesting issue. The basic concept of CSR is very clear: the importance of the social attitude of mining companies towards local communities around mining sites. Conflicts or disputes in the mining industry can have an impact on how well mining companies implement their CSR programs. This research aims to examine the role of CSR in mining company disputes based on applicable law, namely the Limited Liability Company Law and the Mineral and Coal Mining Law, as well as other related legal regulations, in order to encourage companies, especially mining companies to comply with the implementation of CSR in order to avoid mining conflicts/disputes. This research uses a normative juridical method with a statutory approach. This research will explain, review, and assess the laws and regulations related to CSR issues using this methodology and approach. CSR can play a role in preventing and resolving company disputes, including those of mining companies. If a dispute occurs, the provision and implementation of CSR programs can be a bridge solution in resolving mining disputes with the Limited Liability Company Law and the Mineral and Coal Mining Law as the main references.